2018
DOI: 10.1186/s12974-018-1236-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the hepatic Nlrp3 protects dopaminergic neurons via attenuating systemic inflammation in a MPTP/p mouse model of Parkinson’s disease

Abstract: BackgroundParkinson’s disease (PD) is a neurodegenerative disorder with progressive loss of dopaminergic (DA) neurons. Systemic inflammation is shown to initiate and exacerbate DA neuronal degeneration in the substantia nigra. The infiltration and transformation of immune cells from the peripheral tissues are detected in and around the affected brain regions of PD patients. Our previous studies demonstrated the crucial role that microglial Nod-like receptor protein (NLRP) 3 inflammasome plays in the pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 36 publications
(38 reference statements)
0
52
0
Order By: Relevance
“…59 A study also established a link between peripheral inflammation and dopaminergic neuronal loss. 60 Mice injected with lentivirus-wrapped siNlrp3 reduced hepatic inflammasome-mediated cytokine release and prevented it from crossing the BBB and progression of neuroinflammation and damage to DA neurons. 60 α-Synuclein Activates the NLRP3 Inflammasome.…”
Section: Nlrp3 Inflammasome-mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…59 A study also established a link between peripheral inflammation and dopaminergic neuronal loss. 60 Mice injected with lentivirus-wrapped siNlrp3 reduced hepatic inflammasome-mediated cytokine release and prevented it from crossing the BBB and progression of neuroinflammation and damage to DA neurons. 60 α-Synuclein Activates the NLRP3 Inflammasome.…”
Section: Nlrp3 Inflammasome-mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…In mice, activation of microglial NLRP3 inflammasome by misfolded α-synuclein causes the death of proximal dopaminergic neurons. [1,3,[8][9][10][11] The found TiO2 particles are coated with a protein-layer, constituting about 20 % of their mass. TiO2, shown to adsorb and orient peptides and polymers [27][28][29] could also adsorb α-synuclein or its precursor peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the past 5 years have shown that a cause of the degeneration is inflammatory attack of dopaminergic neurons of the substantia nigra by microglia when their NLRP3 inflammasome is activated by phagocytized misfolded α-synuclein. [1][2][3][4][5][6][7][8][9][10][11][12] The misfolded β-sheet-rich α-synuclein aggregates in PD's hallmark Lewy bodies. If misfolded α-synuclein templates the misfolding of more synuclein, it constitutes a PD-propagating prion.…”
Section: Introductionmentioning
confidence: 99%
“…Potential molecular mechanisms that regulate peripheral immune training linked to NLRP3 inflammasome and neurodegeneration are being elucidated. Qiao et al (2018) identified that hepatic NLRP3 inflammasome inhibition by in vivo siRNA administration decreases the TNF-α, IL-β, IL-12, and IL-18 serum levels. Of note, inhibition of the hepatic NLRP3 inflammasome partially prevents dopaminergic neuronal death in the substantia nigra of a murine Parkinson model by decreasing the pro-inflammatory profile in plasma (Qiao et al, 2018).…”
Section: Does Central and Peripheral Innate Immune Training By Nlrp3 mentioning
confidence: 99%
“…Qiao et al (2018) identified that hepatic NLRP3 inflammasome inhibition by in vivo siRNA administration decreases the TNF-α, IL-β, IL-12, and IL-18 serum levels. Of note, inhibition of the hepatic NLRP3 inflammasome partially prevents dopaminergic neuronal death in the substantia nigra of a murine Parkinson model by decreasing the pro-inflammatory profile in plasma (Qiao et al, 2018). It seems that immune activation, at least for viral infections, depends on CXCR6, a chemokine receptor of hepatic NK cells involved in the persistence of cellular memory (Netea et al, 2011).…”
Section: Does Central and Peripheral Innate Immune Training By Nlrp3 mentioning
confidence: 99%